In focus, Hungarian and Central Eastern European characteristics of hunman resource management: An international comparative survey - Mártonné Karoliny; Ferenc Farkas; József Poór (Journal for East European Management Studies, 2009)
The HR practices of the former state-socialist countries have gone through significant changes. The analysis of the developments, built on the Cranet (2004) survey, intends to describe the similarities and differences found between 6 countries of the Central Eastern European region and the total sample of 32 countries participating in the survey. The primary aim of the paper is to highlight the strands of international human resource management, investigating the main focuses, strong and weak elements of both CHRM and HRM. Moreover, it attempts to formulate suggestions on where and how to increase the explanatory power of the current models of CHRM, based on the experiences gained by this analysis. – – Die HR-Praxis in den ehemaligen sozialistischen Ländern hat wesentliche Veränderungen erfahren. Die Analyse der Entwicklungen, die auf der Cranet- Umfrage (2004) aufgebaut sind, zeigt Ähnlichkeiten und Unterschiede zwischen 6 Ländern dieser Region und der Gesamtstichprobe von 32 Ländern. Das primäre Ziele dieses Beitrages liegt darin, den Ist-Zustand und Hauptfokus im internationalen Personalmanagement aufzuzeigen sowie die Stärken und Schwächen von CHRM und HRM zu ermitteln. Darüberhinaus wird versucht, Vorschläge zu formulieren, auf welche Weise und wo die Aussagekraft der aktuellen CHRM-Modelle erhöht werden kann.
Keywords: 650; Comparative Human Resource Management (CHRM); Central Eastern Europe; international comparison; convergences-divergences